Nigeria’s Intergovernmental Relations: A Comparative Analysis of 1963 And 1999 Constitutions - Abraham, Awodokun Ayotunde (Kashere Journal of Politics and International Relations, 2024)
The essential feature of federated States is the division of political power between the federating States and Central Governments. Each tier of government has the final say in respect of matters assigned to it by the constitution. The central and state governments to achieve their set goals, the different levels of government must interact. This interaction of the various levels of government is referred to as intergovernmental relations. This paper Examines Nigeria’s Intergovernmental Relations Under 1963 Republican Constitution and 1999 Constitution, with the aim of determining whether a centralized constitutional provision as we have it under 1999 or decentralized provisions as we had it under 1963 constitution can enhance better intergovernmental relations and facilitates development and healthy competition among states in Nigeria. This study was qualitative in approach and gathered data are content analyzed, using the three-fold typology formulated by Diel S. Wright as framework of analysis. It was discovered that the 1963 constitution gave high level of Autonomy to the regions, and this enhanced development in various dimensions and healthy competition among the Regions, while 1999 constitutional provisions skewed in favour of the federal government as evidenced in the exclusive legislative list and revenue sharing formula. It shows that this present arrangement inhibits pace of development in the country particularly in the areas of social infrastructure, security and even internally generated revenue.